AKUNTABILITAS DAN TRANSPARANSI PENYELENGGARAAN PENGADAAN BARANG/JASA PEMERINTAH PADA SEKRETARIAT DAERAH PROVINSI JAWA BARAT - Ujang A Mukarom; Suryanto; Mia Rumiasari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The problem in this study is how, after implementing electronic procurement as the latest system of goods/services procurement reform, the government can demonstrate accountability and openness in the field of goods/services procurement. This study uses a descriptive qualitative methodology. Purposive sampling is a method for selecting informants used in this research because researchers are trying to get in-depth data from people who really understand the emphasis of the research. The findings of this study show that accountability and transparency are possible. The committee's efforts to be accountable for the entire auction process both vertically and horizontally show that accountability has been realized. The West Java Provincial Government's information about the start of the auction also shows the results of transparency in this research, which helps reduce fraud.